Intelligent Communication and Computational Technologies Proceedings of Internet of Things for Technological Development, IoT4TD 2017 (Lecture Notes in Networks and Systems,, 2018)
The book includes insights that reflect the advances in the field of Internet of Things from upcoming researchers and leading academicians across the globe. It contains the high-quality peer-reviewed papers of 'International Conference on Internet of Things for Technological Development (IoT4TD 2017)', held at Kadi Sarva Vishvavidyalaya, Gandhinagar, Gujarat, India during April 1-2, 2017. The book covers variety of topics such as Internet of things, Intelligent Image Processing, Networks and Mobile Communications, Big Data and Cloud. The book is helpful for the perspective readers' from computer industry and academia to derive the advances of next generation communication and computational technology and shape them into real life applications. .